Nitric Oxide: It’s Role in Immunity - Shailaza Shreshtha; Preeti Sharma; Pradeep Kumar; Rachna Sharma; SP Singh (Journal of Clinical and Diagnostic Research, 2018)
Nitric Oxide (NO), a lipophilic gas synthesised by the enzyme Nitric Oxide Synthase (NOS) from the substrate arginine, is an important biomolecule that mediates cellular signaling. It has a wide spectrum of biological functions including immunomodulation, inflammation, microbial and tumour eradication. Cells of the immune system such as macrophages on activation by cytokines and microbial antigens eradicate a number of microbes or parasites as well as tumour cells by releasing a number of effector molecules which also includes NO. However, this versatile molecule is shown to have dual roles. In lower concentration, this is beneficial and regulates the physiological processes in the body whereas at higher concentrations it is harmful, not only to the microbes or tumor cells but can produce undesirable effects on the host cells too. This suggests that NO has both protective and toxic roles that occur parallel in the body depending upon cellular microenvironment. Therefore, it is very essential to have the knowledge of the physiological processes involved in signaling cascades of NO since it might have novel clinical applications when therapeutic potential of NOS inhibitors and NO donors are to be considered.